The gut-liver axis in hepatobiliary diseases - Masataka Ichikawa; Haruka Okada; Nobuhiro Nakamoto; Nobuhito Taniki; Po-Sung Chu; Takanori Kanai (BMC, 2024)
Abstract Recent advances in the analysis of intestinal bacteria have led to reports of variations in intestinal bacterial levels among hepatobiliary diseases. The mechanisms behind the changes in intestinal bacteria in various hepatobiliary diseases include the abnormal composition of intestinal bacteria, weakening of the intestinal barrier, and bacterial translocation outside the intestinal tract, along with their metabolites, but many aspects remain unresolved. Further research employing clinical studies and animal models is expected to clarify the direct relationship between intestinal bacteria and hepatobiliary diseases and to validate the utility of intestinal bacteria as a diagnostic biomarker and potential therapeutic target. This review summarizes the involvement of the microbiota in the pathogenesis of hepatobiliary diseases via the gut-liver axis.